Drug-induced urticaria (DIU) and angioedema in Latin American Countries - Jares, Edgardo J.; Sanchez-Borges, Mario; Gomez, R. Maximiliano; Serrano, Carlos D.; Ensina, Luis Felipe C.; Ojeda, Ivan Cherrez; Bernstein, Jonathan A.; De Falco, Alicia Mabel; Cuello, Mabel Noemi; Del Refugio Morfin Maciel, Blanca Maria; Cruz, Alfredo Arias; Villa, Ricardo Cardona; et al. (Journal of allergy and clinical immunology, 2018)
Methods A retrospective, cross-sectional study assessed characteristics of drug induced urticaria (DIU) and angioedema using the European Network of Drug Allergy questionnaire in 22 allergy units from 11 Latin American countries. The most frequently reported DIU inducers were nonsteroidal anti-inflammatory drugs (NSAIDs) (68%) followed by beta lactam (13%) and non-beta lactam (8%) antibiotics.